Studies on Chemical Reduction of Ag-Pd Alloy Powder by Hydrazine from Silver and Palladium Nitrate Solution - Katoh, Osamu; Takagi, Shinobu; Shimizu, Takayoshi (DENKI-SEIKO, 1991)
Ag-Pd alloyed fine powders were prepared by the chemical reduction in the liquid phase using N2H2. The effect of N2H2 concentration, metal ion concentration, pH and solution temperature on the size and the shape of the particles were investigated. The results obtained are as follows; (1) Reduction of Ag-Pd proceeds to completion only when the NH3/metal molar ratio is more than 0.8. (2) The higher the pH, the narrower the particle size distribution. (3) The higher the concentration of metal ion in the solution, the larger the particle. (4) Spherical particles are formed when the temperature is in the range of about 10 to 30°C.